Effectiveness of body awareness interventions in fibromyalgia and chronic fatigue syndrome: A systematic review and meta-analysis. Issue 1 (January 2015) - Courtois, Imke; Cools, Filip; Calsius, Joeri
Summary Objectives Patients with long-lasting pain problems often complain of lack of confidence and trust in their body. Through physical experiences and reflections they can develop a more positive body- and self-experience. Body awareness has been suggested as an approach for treating patients with chronic pain and other psychosomatic conditions. The aim of this systematic review is to assess the effectiveness of body awareness interventions (BAI) in fibromyalgia (FM) and chronic fatigue syndrome (CFS). Methods Two independent readers conducted a search on Medline, Cochrane Central, PsycINFO, Web of knowledge, PEDro and Cinahl for randomized controlled trials. Results We identified and screened 7.107 records of which 29 articles met the inclusion criteria. Overall, there is evidence that BAI has positive effects on the Fibromyalgia Impact Questionnaire (FIQ) (MD −5.55; CI −8.71 to −2.40), pain (SMD −0.39, CI −0.75 to −0.02), depression (SMD −0.23, CI −0.39 to −0.06), anxiety (SMD −0.23, CI −0.44 to −0.02) and Health Related Quality of Life (HRQoL) (SMD 0.62, CI 0.35–0.90) when compared with control conditions. The overall heterogeneity is very strong for FIQ (I2 92%) and pain (I2 97%), which cannot be explained by differences in control condition or type of BAI (hands-on/hands-off). The overall heterogeneity for anxiety, depression and HRQoL ranges from low to moderate (I2 0%–37%). Conclusions Body awareness seems to play an important role in anxiety, depression and HRQoL. Still, interpretations have to be done carefully since the lack of high quality studies.